Solve zx+zy = z2 with the initial conditions z(x, 0)=f(x)
P=1
Q=1
R=z2
"\\frac{dx}{P}=\\frac{dy}{Q}=\\frac{dz}{R}"
"\\frac{dx}{1}=\\frac{dy}{1}=\\frac{dz}{z^2}"
Multiplyers: -z2,1,1
-z2dx+dy+dz=0
-z2x+y+z=C1
Multiplyers: 1,-z2,1
dx-z2dy+dz=0
x-z2y+z=C2
The general solution is,
"\\phi(c_{1},c_{2})=0"
"\\phi( -z^2x+y+z),(x-z^2y+z)=0"
-z2x+z+y-C1=0
D=1+4x(y-C1)
"z_1=\\frac{-1+\\sqrt{1+4x(y-C_1)}}{-2x}=\\frac{-1+\\sqrt{1-4xC_1}}{-2x}=f(x)"
"\\sqrt{1-4xC_1}=-2xf(x)+1"
"4xC_1=-{(-2xf(x)+1)}^2+1"
"C_1(1)=\\frac{-{(-2xf(x)+1)}^2+1}{4x}"
"z_2=\\frac{-1-\\sqrt{1+4x(y-C_1)}}{-2x}=\\frac{-1-\\sqrt{1-4xC_1}}{-2x}=f(x)"
"\\sqrt{1-4xC_1}=2xf(x)-1"
"4xC_1=-{(2xf(x)-1)}^2+1"
"C_1(2)=\\frac{-{(2xf(x)-1)}^2+1}{4x}"
-z2y+z+x-C2=0
As y=0
z=C2 - x= f(x)
C2=f(x) + x
Comments
Leave a comment